Predictors of Literacy Development in Adulthood: Insights from a Large-scale, Two-wave Study - Wicht, Alexandra [Verfasser]; Rammstedt, Beatrice [Verfasser]; Lechner, Clemens M. [Verfasser] (My University, 2020)
"This study aims to illuminate factors that explain changes in literacy skills across up to six years of adulthood, using data from two waves of the German National Educational Panel Study (NEPS; N = 4,359). More specifically, we gauge the relative importance of three groups of factors that previous research and theorizing have highlighted as possible predictors of changes over time in literacy: Socio-demographic characteristics, literacy practices, and basic cognitive abilities. Three key findings emerge from our analyses: (1) literary practices predict gains in literacy, in line with the “use it or lose it” hypothesis; (2) sociodemographic factors that reflect higher resources and skills (particularly, high formal education and German as mother tongue) predict gains in literacy, resembling a “Matthew effect”; (3) lower basic cognitive abilities predict higher losses in literacy, consistent with the “general slowing” hypothesis of cognitive aging." (Author's abstract ; BIBB-Doku)
Keywords: P 1.2 Erwachsene; 370; Lesekompetenz; Schreibkompetenz; Soziodemografische Faktoren; Kognitive Fähigkeit; Erwachsener; Nationaler Bildungsbericht